KARAKTERISTIK LUKA PADA KORBAN KECELAKAAN LALU LINTAS YANG MENINGGAL DI BAWA KE RUMAH SAKIT UMUM DAERAH Drs. H. AMRI TAMBUNAN - FITRI APRIANTA; ABDUL GAFAR (JURNAL ILMIAH KOHESI, 2023)
The incidence of traffic accidents is a health problem in the field of forensic medicine that often occurs in society and needsspecial attention because it is still a major problem in the implementation of road transportation in Indonesia. According toAccording to the World Health Organization (WHO) 2018 report, 1.35 million people die every year due to traffic accidentsworldwide. This research aims to determine the characteristics of the injuries sustained by traffic accident victims who died.the Regional General Hospital, Drs. H. Amri Tambunan, 2020–2021. This study used a descriptive method using aIn the retrospective design, the sampling method used was a total sampling technique. The data of this study were obtained fromsecondary data. Population and sampel of 20 victims (total population). The results showed that the most victims died fromtraffic accidents in the male gender (95,0%), the age of the victim was at most 17–25 years (35,0%), and the location of theinjuries were the most common (80,0%); the most common types of injuries were lacerations, abrasions, and fractures (50,0%). TheThe conclusion of this study is that the victims of traffic accidents who died were taken to the Regional General Hospital, Drs. H.Amri Tambunan is the most male, 17–25 years old, The location of the most injuries is the hand and the type of wound is atorn wound.